Implementasi Kegiatan Muhadhoroh Dalam Meningkatkan Kecerdasan Linguistik Santri Pondok Pesantren At-Taqwa - Ahmad Muidal; Akmal Rizki Gunawan Hasibuan; Abdurrahman Siddiq (Turabian: Jurnal Pendidikan Islam, 2023)
This study examines two problems, namely the implementation of muhadhoroh activities in improving the linguistic intelligence of students and efforts to improve linguistic intelligence in muhadhoroh activities. This study aims to determine the results of the implementation of muhadhoroh activities in improving the linguistic intelligence of students at Pondok Pesantren At-Taqwa Bekasi. Data obtained through observation, interviews and documentation. Data analysis in this study is a qualitative descriptive analysis technique, namely, data analysis methods in the form of words, pictures, and not numbers. The results showed that linguistic intelligence is generally influenced by the environment and the individual. In particular, language is influenced by (a) the ability to master intonation and tempo. (b) the ability to compose speech texts. (c) the ability to harmonize language using standard and non-standard words. Efforts that can be made to improve the linguistic intelligence of students are carried out by practicing regularly and seriously. Efforts to overcome linguistic problems, namely by presenting groups of students who are proficient in speech with the aim of motivating other students to foster a desire to improve the linguistic abilities of students in muhadhoroh, while Asatidz as a supervisor who provides direct guidance and evaluation to students at the end of each muhadhoroh activity.